PRAKTEK DEMOKRASI DALAM SISTEM PEMERINTAHAN TUâA GOLO (Studi Tentang Demokrasi Tradisonal Masyarakat Suku Manggarai, Propinsi Nusa Tenggara Timur) - , Venansius Heronaldus Hambut ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The main topic that will be discussed in this thesis is about the democracy that is practiced in the administration system of "Tu'a Golo" especially in Manggaraian society. However, this writing is not just limited to talk about democracy. This paper also discusses the dynamics of Golo it self in relation to the political supra of Golo, either it is fenceless or be closed. Therefore, there are two main questions to be answered in this writing. First, how is the practice of democracy in Manggaraian society in the Governance System of Tu'a Golo? Second, how the relationship between Golo and SupraGolo in the context of the political system of supra Golo, overt and covert? To answer those two questions, the authors used two theories, namely the theory of democratic distribution of resources that is proposed by Tatu Van Hanen and the theory about informal institutions that is taken from Hans Joachim Lougth writing "Informal institutions and Democracy" and the writing of Gretchen Helmke and Steven Levitsky"informal Institutions and Comparative Politics: A Research Agenda ". While the research method used by the writer is descriptive method and historical research. The findings in this study are as follows, first, found the practice of democracy in the governance system of Tu'a Golo. This is further evidenced by the practice of distribution of agricultural land through the mechanism in Lodok Lingko. This mechanism ensures the distribution of agricultural land in a fair and equitable to all the citizens of Golo, where every patriarch will gain the land with the same number and size. Second, the pattern of relations between Golo and Supra Golo in the context of the political system which is covered in the shape of two models, the models are: complementary relationship patterns and accommodating. Complementary relationship is happened since the era of kingdom until the last colonial period. This pattern of relation impliesapositive effect to the institution of Golo, where Golo is exists as a system of localgovernment, because of its positionis accommodated and placed as a part of the governance System of Supra Golo.While the pattern of relationship that is Accommodative occur in the new orde era. Such apattern of relationships is emergingas a reflection on theimpotenceof local institutionsin the face of a powerful state and authoritarian, so there is no other choice for Golo besides accepting the presence of the state and try to survive the ons laught of the existingrange. The implication of this is Golo is almost total bankruptcy, however, this institutionstill able to survivemainly because there are other spaces that can not affordtheco-optation by the State, namely the position Golo as the customary land authorities and the customary institutions. Third, in the context of political system of supra Golo which is overt to the form of relationship between Golo and supra Golo, which is running in a competitive relationship, bet ween Golo and the government competing with each other even in diametrical face to face. In addition to this reality olso provides an overview of post-reform state condition which is very weak, also gives the negative impact for the future of Golo it self, where the citizens in the Golo get stuck in the vortex of a long conflict with no clear result, this situation eventually led to the apathy of Golo residents to this institution. This situation is exacerbated by the political and economic presence in the dynamic of Golo, although the pattern of relationship that is built up between Golo with those two communities is complementary, but the presence of those two communities could lead the Golo to the disintegration in the future totally. The presence of the political community has made Golo as an arena of battle interests among the political actors.This situation led to internal divisions in Golo. While the presence of economic society led to deterioration of cultural values and changes in occupational structure over communal land as the main resource and the basic power of Golo.